2018
DOI: 10.1186/s12880-018-0272-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional brain changes in perimenopausal women who are susceptible to migraine: a study protocol of multi-modal MRI trial

Abstract: BackgroundAs a common clinical symptom that often bothers midlife females, migraine is closely associated with perimenopause. Previous studies suggest that one of the most prominent triggers is the sudden decline of estrogen during perimenopausal period. Hormone replacement therapy (HRT) is widely used to prevent this suffering in perimenopausal women, but effective diagnostic system is lacked for quantifying the severity of the diseaase. To avoid the abuse and overuse of HRT, we propose to conduct a diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Furthermore, migraines related to menstrual episodes are considered more disabling and less responsive to treatment than non-menstrual episodes [ 28 ]. Recent brain fMRI studies supported the existence of functional differences between women and men, between migraine patients and HCs, and between female migraine patients with different hormone levels [ 6 , 29 ]. One study suggested that the FC impairments of the ACC were significantly correlated with pain severity, and pain-associated emotional disorders in menstrual migraine patients and, therefore, the ACC might be an important biomarker to differentiate migraines from HCs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, migraines related to menstrual episodes are considered more disabling and less responsive to treatment than non-menstrual episodes [ 28 ]. Recent brain fMRI studies supported the existence of functional differences between women and men, between migraine patients and HCs, and between female migraine patients with different hormone levels [ 6 , 29 ]. One study suggested that the FC impairments of the ACC were significantly correlated with pain severity, and pain-associated emotional disorders in menstrual migraine patients and, therefore, the ACC might be an important biomarker to differentiate migraines from HCs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous studies [17,23], PASS software was used to calculate the sample size. A sample size of 40 patients in each group will be suitable for a power of 0.8 and an alpha signi cance at the level of 0.05 (two-sided).…”
Section: Subjectsmentioning
confidence: 99%